Magic in News: Magic, Witchcraft and Superstition in Estonian Newspapers 1850-1980 - Jonuks, Tõnno (The pomegranate, 2023)
This study discusses magic and witchcraft as presented in late nineteenth and early twentieth-century newspaper articles in Estonia. Magic is understood according to its vernacular meaning, including witchcraft, magic, and healing but also fraud, which created a solid but amorphous concept for the common people at this period. A diachronic overview emphasizes how perceptions of magic have changed during time. The material is divided into three groups, covering folkloric, authority-related, and educational reactions to magical acts. According to the material discussed in this article, the majority of relevant news was published because of curiosity, and the dominating attitude is to ridicule the persons who have performed or participated in some magical act.